Assessment of Solar Box Cooker (SBC) with Kapok fiber insulator under Maiduguri Weather Conditions - Abdulrahim, A. T.; Abdulkareem, S.; Haruna, M.; Maina, M. B.; Abdulraheem, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This paper presents the construction and performance evaluation of solar box cooker with kapok insulator. The solar cooker offers an economically viable alternative while mitigating environment degradation due to excessive use of biomass/conventional energy sources for cooking purposes. The Bureau of Indian Standard (BIS: IS B429) was used to determine the thermal performance parameters of the cooker, where first figure of merit (F1) and second figure of merit (F2) were determined to be F1= 0.132 and F2= 0.58. The cooker thermal efficiency (η) = 44%, qualifying the cooker to be grade “A” according to BIS. The American Society of Agricultural and Biological Engineers for Solar Cooking (ASAE S580.1) was used to determine the cookers cooking power and it was found to be (Ps) =14.7W while the (R2) value was 0.137 coefficient of regression.